2014
DOI: 10.1371/journal.pone.0100821
|View full text |Cite
|
Sign up to set email alerts
|

B-MOBILE - A Smartphone-Based Intervention to Reduce Sedentary Time in Overweight/Obese Individuals: A Within-Subjects Experimental Trial

Abstract: PurposeExcessive sedentary time (SED) has been linked to obesity and other adverse health outcomes. However, few sedentary-reducing interventions exist and none have utilized smartphones to automate behavioral strategies to decrease SED. We tested a smartphone-based intervention to monitor and decrease SED in overweight/obese individuals, and compared 3 approaches to prompting physical activity (PA) breaks and delivering feedback on SED.Design and MethodsParticipants [N = 30; Age  = 47.5(13.5) years; 83% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
210
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(223 citation statements)
references
References 32 publications
5
210
1
6
Order By: Relevance
“…Several other trials have demonstrated promise in reducing sedentary time among office workers using various interventions that include computer software [26], computer software and text messages [30], sit-stand workstations [23,31], portable pedal bike [24], or an in-person session [32]. Furthermore, the magnitude of changes in sedentary time and light activity in the current trial (sedentary change, −8.1 %; light activity change, 7.9 %) were slightly larger than those seen in a recent trial by Bond et al [33] that used similar technology to interrupt sedentary time (sedentary change, -3.3 to −5.9 %; light activity change, 2.7 to 4.7 %).…”
Section: Discussioncontrasting
confidence: 68%
“…Several other trials have demonstrated promise in reducing sedentary time among office workers using various interventions that include computer software [26], computer software and text messages [30], sit-stand workstations [23,31], portable pedal bike [24], or an in-person session [32]. Furthermore, the magnitude of changes in sedentary time and light activity in the current trial (sedentary change, −8.1 %; light activity change, 7.9 %) were slightly larger than those seen in a recent trial by Bond et al [33] that used similar technology to interrupt sedentary time (sedentary change, -3.3 to −5.9 %; light activity change, 2.7 to 4.7 %).…”
Section: Discussioncontrasting
confidence: 68%
“…Figure 2 trial or outcome studies, five articles focused on software design and evaluation and the remaining articles are on focus groups and interview studies on stakeholders' opinions on smart phone apps for physical activity (see Table 1). [25] × × [26] × [27] × × × × × × × × × [28] × × × × × × × × [29] × × × × [30] × × × [31] × [32] × × × × × × × × × × × × [33] × × [34] × × × × × × × [35] × × × × [36] × × × × × × [37] × [38] × × × [39] × × × × × [40] × [41] × [42] × × × × [43] × × [44] Illustrations in figure 2 and table 2 show features that are highly present in articles on physical activity intervention studies, those features that were occasionally mentioned, or those that were not cited often in these articles. Visualisation of persuasive features is presented to provide more insights about the highlights, 9 gaps and blank spots [45] in current mobile application persuasive design features on physical activity.…”
Section: Data Extractionmentioning
confidence: 99%
“…Self-monitoring was implemented in the form of manual logging [27] or automatic tracking of physical activity [30], either in terms of step count [29], distance travelled [30], active time [31] or sedentary time [25], or other self-evaluation criteria. A qualitative study of user's attitudes towards mobile application promoting physical activity indicated that selfmonitoring is considered to be an important tool in behaviour modification [28].…”
Section: Primary Task Supportmentioning
confidence: 99%
See 2 more Smart Citations